Lower immunity to poliomyelitis viruses in Australian young adults not eligible for inactivated polio vaccine. Issue 11 (4th March 2020) - Hendry, Alexandra J.; Beard, Frank H.; Dey, Aditi; Quinn, Helen; Hueston, Linda; Dwyer, Dominic E.; McIntyre, Peter B.
Abstract: There are limited long-term data on seroprevalence of neutralising antibody (nAb) to the three poliovirus serotypes following the switch from oral polio vaccine (OPV) to inactivated polio vaccine (IPV). In Australia, combination vaccines containing IPV replaced OPV in late 2005. Using serum and plasma specimens collected during 2012 and 2013, we compared prevalence of nAb to poliovirus type 1 (PV1), type 2 (PV2) and type 3 (PV3) in birth cohorts with differing IPV and OPV eligibility from an Australian population-based sample. In the total sample of 1673 persons aged 12 months to 99 years, 85% had nAb against PV1, 83% PV2 and 67% PV3. In the cohort 12 to <18 years (eligible for 4 OPV doses, last dose 8–14 years prior), a significantly lower proportion had nAb than in the 7 to <12 year cohort (eligible for 3 OPV doses and an IPV booster, last dose 3–8 years prior) for all poliovirus types: [PV1: 87.1% vs. 95.9% (P = 0.01), PV2: 80.4% vs. 92.9% (P = 0.003) and PV3: 38.1% vs. 84.0% (P < 0.0001)]. These data suggest individual-level immunity may be better maintained when an OPV primary schedule is boosted by IPV, and support inclusion of an IPV booster in travel recommendations for young adults who previously received only OPV.